«Two suns cannot shine under the same sky». The Guayaquil interview between José de San Martin and Simón Bolívar (1822) - Pérez Valdivia , Javier (2021)
The aim of this research is to examine the so-called Guayaquil Interview held between José de San Martín and Simón Bolívar on July 26 and 27, 1822. Using a variety of historical sources, we have been able to clarify the backgrounds, rebuild the ex post facto agenda, clarify the leit motiv of some decisions, identify some consequences and evaluate their political, military and historical relevance as a turning point in the South American independence process.